Selective deoxygenation of sludge palm oil into diesel range fuel over Mn-Mo supported on activated carbon catalyst - Abdulkareem Ghassan Alsultan; Nurul Asikin-Mijan; Laith K. Obeas; Aminul Islam; Nasar Mansir; Teo, Siow Hwa; Siti Zulaika Razali; Maadh F. Nassar; Surahim Mohamad; Yap, Yun Hin Taufiq (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Originating from deoxygenation (DO) technology, green diesel was innovated in order to act as a substitute for biodiesel, which contains unstable fatty acid alkyl ester owing to the existence of oxygenated species. Green diesel was manufactured following a process of catalytic DO of sludge palm oil (SPO). An engineered Mn(0.5%)-Mo(0.5%)/AC catalyst was employed in a hydrogen-free atmosphere. The influence of Manganese (Mn) species (0.1–1 wt.%) on DO reactivity and the dissemination of the product were examined. The Mn(0.5%)-Mo(0.5%)/AC formulation gave rise to a superior harvest of approximately 89% liquid hydrocarbons; a higher proportion of diesel fraction selectivity n-(C15 +C17) was obtained in the region of 93%. Where acid and basic active sites were present on the Mn(0.5%)-Mo(0.5%)/AC catalyst, decarboxylation and decarbonylation reaction mechanisms of SPO to DO were enhanced. Evidence of the high degree of stability of the Mn(0.5%)-Mo(0.5%)/AC catalyst during five continuous runs was presented, which, in mild reaction conditions, gave rise to a consistent hydrocarbon harvest of >72% and >94% selectivity for n-(C15 +C17).